Analisis Keusangan dan Paro Hidup Literatur pada Jurnal Intizar Tahun 2013-2020 - Elvira Marcelis; Herlina Herlina; Mulyadi Mulyadi (Syarif Hidayatullah State Islamic University of Jakarta, INDONESIA, 2022)
This study examines the Intizar Journal using Bibliometric studies, namely Literature Obsolescence and Literature Half Life. Bibliometric study of this journal is important because it is to find out the development of Contemporary Thought and Islamic Studies and Muslims. The purpose of this study was to determine the level of obsolescence of the literature cited in each scientific article published in the Intizar Journal in 2013-2020, and to determine the level of up-to-date information contained in the Intizar journal in terms of the half-life size of the document literature cited in 2013 -2020. This research is a type of descriptive research with a quantitative approach. Sampling using a total sampling technique or the entire population being studied is used as a sample, the sample in this study is all citations in the Intizar Journal 2013-2020. There are 140 articles with a total of 2305 citations. The results obtained from the calculations that have been carried out show that the highest level of literature obsolescence in the Intizar Journal in 2013-2020 is in volume 22 number 2 in 2016 which is 49.3%, while the lowest level of literature obsolescence is in the Journal. Intizar in 2013-2020 is contained in volume 19 number 2 in 2013 which is 15.7%. The highest half-life of the Intizar Journal Literature occurred in volume 21 number 2 in 2015 which was 24.02 years, while the lowest half-life occurred in volume 25 number 1 in 2019, which was 7.4 years, based on the calculation of the Literature Half-Life in the Intizar Journal. 2013-2020 is 12.11 years.